2013
DOI: 10.1037/a0031198
|View full text |Cite
|
Sign up to set email alerts
|

Sudden gains in cognitive therapy and interpersonal therapy for social anxiety disorder.

Abstract: Sudden gains in CT and IPT for SAD are predictive of long-term outcome. In addition, the effect of sudden gains may be greater in CT compared to IPT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
48
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 19 publications
9
48
3
1
Order By: Relevance
“…Although there is some support for this assumption coming from treatment studies for depression (e.g. Tang & DeRubeis, 1999; Tang et al, 2005), cognitive change was not predictive of SGs in studies examining behavioural activation (Hunnicutt-Ferguson, Hoxha, & Gollan, 2012) or supportive-expressive therapy for depression (Andrusyna, Luborsky, Pham, & Tang, 2006) or CBT for social anxiety disorder (Hofmann, Schulz, Meuret, Moscovitch, & Suvak, 2006; Bohn, Aderka, Schreiber, Stangier, & Hofmann, 2013). It is possible that SGs are more likely to emerge as treatment mediators in interventions that place a relatively great focus on modifying maladaptive beliefs, such as CBT for depression as compared to other treatments, such as those that are focused on an exposure-extinction paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is some support for this assumption coming from treatment studies for depression (e.g. Tang & DeRubeis, 1999; Tang et al, 2005), cognitive change was not predictive of SGs in studies examining behavioural activation (Hunnicutt-Ferguson, Hoxha, & Gollan, 2012) or supportive-expressive therapy for depression (Andrusyna, Luborsky, Pham, & Tang, 2006) or CBT for social anxiety disorder (Hofmann, Schulz, Meuret, Moscovitch, & Suvak, 2006; Bohn, Aderka, Schreiber, Stangier, & Hofmann, 2013). It is possible that SGs are more likely to emerge as treatment mediators in interventions that place a relatively great focus on modifying maladaptive beliefs, such as CBT for depression as compared to other treatments, such as those that are focused on an exposure-extinction paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…Tang and DeRubeis () were the first to quantitatively define positive discontinuous symptom changes throughout the course of treatment and found that sudden gains were associated with better treatment outcome at termination and follow‐up. Following research confirmed these results and showed that sudden gains are a frequent phenomenon among patients with different disorders like depression (Hardy et al, ; Lutz et al, ; Tang, DeRubeis, Beberman, & Pham, ), social anxiety disorder (Bohn, Aderka, Schreiber, Stangier, & Hofmann, ; Hofmann, Schulz, Meuret, Moscovitch, & Suvak, ), generalized anxiety disorder (Deschênes & Dugas, ), posttraumatic stress disorder (Aderka, Appelbaum‐Namdar, Shafran, & Gilboa‐Schechtman, ; Doane, Feeny, & Zoellner, ; Krüger et al, ), or obsessive‐compulsive disorder (Aderka, Nickerson, Bøe, & Hofmann, ). A meta‐analysis also showed that the occurrence of sudden gains within a therapy predicts significantly better outcomes at the end of therapy (Aderka et al, ).…”
Section: Introductionmentioning
confidence: 74%
“…However, participants in individual cognitive therapy reported more improvement than those in intensive group cognitive therapy or TAU (Mortberg et al, 2007). In addition, in a study of sudden gains in cognitive therapy and interpersonal therapy for SAD, participants who experienced a sudden gain during either treatment reported significant decreases in the frequency and strength of their negative thoughts following the gain (Bohn, Aderka, Schreiber, Stangier, & Hofmann, 2013).…”
Section: Self-statementsmentioning
confidence: 97%